Comparison between Ultrasound and Fluoroscopy-guided Percutaneous Nephrolithotomy (PCNL) at Raden Mattaher Jambi Hospital - Randy Fauzan; Raga Manduaru; Ardiansyah Periadi Sitompul; Wendi Rachman; Hendra Herman (African Journal of Urology, 2023)
Abstract Purpose To investigate the effectiveness and safety of ultrasound-guided and Percutaneous Nephrolithotomy (PCNL) compared to the standard fluoroscopy-guided PCNL. Methods This study is a comparative retrospective study obtained from medical records within the last 5 years of Raden Mattaher Hospital, Jambi. Patients were divided into 2 groups, fluoroscopy- and ultrasonography-guided PCNL with large kidney stone > 20 mm. Patient characteristics were divided into pre- and post-operative procedures and analyzed using SPSS ver. 25.0 (SPSS Inc., Chicago, IL, USA). Data were analyzed using Kolmogorov–Smirnov, chi-square and/ Fischer’s exact test and p value < 0.05 was considered statistically significant. Results Of 201 patients’ data from medical records were divided into ultrasound-guided and fluoroscopy-guided groups. Ultrasound-guided group were consisted of 89 patients and fluoroscopy-guided were of 112 patients. US Guided significantly identifies the severity of hydronephrosis compared to PCNL. The demographic data obtained age, sex, body mass index, and preoperative hemoglobin levels showed a normal distribution. On the post-operative results, significant results occurred in post-PCNL stent placement. Installation of a DJ stent alone is more commonly performed on fluoroscopy-guided PCNL procedures compared to ultrasound-guided PCNL. This had a positive impact on post-procedure outcomes, meaning that the post-operative outcome of ultrasound-guided PCNL was better than that of fluoroscopy-guided PCNL. Conclusion The reported data demonstrate that PCNL and ultrasound-guided has similar efficacy and complication rates with PCNL fluoroscopy-guided. This could be a good alternative in urological centers with no access to fluoroscopy. However, ultrasound-guided group was still associated with higher rate nephrostomy tube placement and longer surgery duration.